Simulation of Models for Multifunctional Photopolymerization Kinetics - ÇİFTÇİOĞLU, GÖKÇEN ALEV (WILEY-BLACKWELL, 2014)
In this study, two different models of photopolymerization of multifunctional monomers are developed. The first is a kinetic model and is based on first order nonlinear ordinary differential equations describing the rates of photoinitiator, monomer, and live and dead radicals of different chain lengths. In the second model, a stochastic Monte Carlo approach is used to predict the time evolution of the photopolymerization process. In this model the chain affects are incorporated both in the propagation and termination rate constants. The simulations of these models for the predictions of gelation times are compared with the experimental values measured in the absence of oxygen in the reaction volume by using passive microrheology technique. The nonlinear decrease of gelation time with increasing photoinitator concentration and number of acrylate fragments on each monomer is best captured with the second model. Furthermore, the second model is successfully verified with kinetic data generated from FTIR and DSC experiments. (C) 2013 Society of Plastics Engineers
Keywords: COUPLED CHEMICAL-REACTIONS; POLYMERIZATION; MONOMERS